Review of gait control and closed-loop motion control methods for bionic robotic fish - Wenqian WANG; Penglei MA; Guanghao LI; Chuanxin XU; Bing YAO; Guijie LIU (Zhongguo Jianchuan Yanjiu, 2024)
The advantages of fish such as high propulsion efficiency, strong maneuverability and low environmental disturbance have sparked extensive research on bionic robotic fish by both domestic and international scholars. The basic-level gait control method and closed-loop motion control method are currently two hot topics in research on robotic fish control. According to the propulsion mode classification method, this paper summarizes the prototype development and performance of various robotic fish, introduces the research progress of the propulsion mechanisms and hydrodynamics of robotic fish, focuses on two basic gait control ideas, namely the trajectory approximation method and central pattern generator （CPG）, and summarizes the typical closed-loop motion control method. The CPG method has stronger flexibility, stability and operability, and it is easy to introduce feedback items and achieve closed-loop control, for which it plays a leading role in the basic gait control of robotic fish; while the improved learning-based control method and hybrid control method combining multiple methods based on the significant characteristics of robotic fish have broader development prospects, which is in line with the development direction of intelligent biomimetic robotic fish. Establishing a reasonable gait control system and an accurate and efficient closed-loop motion control system based on working conditions and motion requirements is the key to improving the overall performance of robotic fish.